Mapping subcortical brain lesions, behavioral and acoustic analysis for early assessment of subacute stroke patients with dysarthria - Liu, Juan; Ruzi, Rukiye; Jian, Chuyao; Wang, Qiuyu; Zhao, Shuzhi; Ng, Manwa L.; Zhao, Shaofeng; Wang, Lan; Yan, Nan (Frontiers in Neuroscience, 2025)
IntroductionDysarthria is a motor speech disorder frequently associated with subcortical damage. However, the precise roles of the subcortical nuclei, particularly the basal ganglia and thalamus, in the speech production process remain poorly understood.MethodsThe present study aimed to better understand their roles by mapping neuroimaging, behavioral, and speech data obtained from subacute stroke patients with subcortical lesions. Multivariate lesion-symptom mapping and voxel-based morphometry methods were employed to correlate lesions in the basal ganglia and thalamus with speech production, with emphases on linguistic processing and articulation.ResultsThe present findings revealed that the left thalamus and putamen are significantly correlated with concept preparation (r = 0.64, p < 0.01) and word retrieval (r = 0.56, p < 0.01). As the difficulty of the behavioral tasks increased, the influence of cognitive factors on early linguistic processing gradually intensified. The globus pallidus and caudate nucleus were found to significantly impact the movements of the larynx (r = 0.63, p < 0.01) and tongue (r = 0.59, p = 0.01). These insights underscore the complex and interconnected roles of the basal ganglia and thalamus in the intricate processes of speech production. The lateralization and hierarchical organization of each nucleus are crucial to their contributions to these speech functions.DiscussionThe present study provides a nuanced understanding of how lesions in the basal ganglia and thalamus impact various stages of speech production, thereby enhancing our understanding of the subcortical neuromechanisms underlying dysarthria. The findings could also contribute to the identification of multimodal assessment indicators, which could aid in the precise evaluation and personalized treatment of speech impairments.